PENGARUH KINERJA KEUANGAN TERHADAP KINERJA EKONOMI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Laili, Siti Nur; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of financial performance to the economic performance. Thefinancial performance is measured by using financial ratio. The financial ratio in this research is liquidity ratiowhich is proxy by current assets, leverage ratio is proxy by debt to equity ratio, profitability ratio is proxy byreturn on assets, and activity is proxy by total assets turnover. Meanwhile, the economic performance ismeasured by using market variable standard i.e. stock price. The population of this research is 144manufacturing companies which are listed in Indonesia Stock Exchange in 2011-2015. The sample collectiontechnique has been done by using purposive sampling method and 37 samples during 2011-2015 have beenobtained. The data has been conducted by using secondary data which has been selected by using documentationtechniques which consist of 2011-2015 manufacturing company annual report. The data analysis method of thisresearch has been carried out by using multiple linear regressions analysis.The result of this research shows thatliquidity ratio, leverage and activity do not give any influence to the economic performance whereas theprofitability ratio gives influence to the economic performance.Keywords: Liquidity ratio, leverage, profitability, activity, economic performance.